Coupled multimodal fluid-vehicle model for analysis of anti-slosh effectiveness of longitudinal baffles in a partially-filled tank vehicle. (April 2017) - Kolaei, Amir; Rakheja, Subhash; Richard, Marc J.
Abstract: An efficient model is formulated for analysis of a coupled fluid slosh-vehicle dynamic system to study the effects of different baffle designs on directional dynamic performance of a partially-filled tank vehicle. A multimodal model of fluid sloshing within a baffled cylindrical tank is initially formulated using potential flow equations and linearized free-surface boundary condition considering maneuver-induced vehicle motions along the lateral, vertical and roll axes. Natural slosh modes/frequencies, hydrodynamic coefficients and Stokes-Joukowski potential associated with the multimodal model are then obtained by solving the eigenvalue problem of free fluid sloshing using a higher order boundary element method. Significant improvement in computational time is achieved by reducing the generalized eigenvalue problem to a standard one involving only the velocity potentials on the half free-surface length using the zoning method. The hydrodynamic force and moment obtained from the multimodal model are subsequently coupled with the TruckSim vehicle dynamic simulation platform through a MATLAB/Simulink model to obtain dynamic responses of a partially-filled tank vehicle with and without baffles under step-turn and double-lane change maneuvers. Two different designs of longitudinal baffles are considered: bottom- and top-mounted baffles. The validity and efficiency of the present boundary element method is demonstrated by comparing the results with those obtained using the boundary element method employing linear elements. The effective mass moment of inertial of the fluid in a clean-bore tank is also obtained as a function of fill ratio and compared with the reported analytical solutions for a half-full tank to further verify the model. The results suggest that directional dynamic responses of partly-filled tank vehicles can be efficiently analyzed using the coupled multimodal slosh-vehicle models with significantly lower computational effort than the methods employing computational fluid dynamic (CFD) fluid slosh models. The results further reveal that top-mounted baffles are most effective in suppressing the fluid slosh force under more likely loading conditions in road tankers.